A refined search for pulsations in white dwarf companions to millisecond pulsars - Kilic, Mukremin (2018)
We present optical high-speed photometry of three millisecond pulsars with low-mass (< 0.3M⊙)white dwarf companions, bringing the total number of such systemswith follow-up time-series photometry to five. We confirm the detection of pulsations in one system, the white dwarf companion to PSR J1738+0333, and show that the pulsation frequencies and amplitudes are variable over many months. A full asteroseismic analysis for this star is underconstrained, but the mode periods we observe are consistent with expectations for anM = 0.16-0.19M⊙ white dwarf, as suggested from spectroscopy. We also present the empirical boundaries of the instability strip for low-mass white dwarfs based on the full sample of white dwarfs, and discuss the distinction between pulsating low-mass white dwarfs and subdwarf A/F stars.